1999
DOI: 10.1017/s0007114599001294
|View full text |Cite
|
Sign up to set email alerts
|

Ileal amino acid digestibilities in pigs of barley-based diets with inclusion of lucerne (Medicago sativa), white clover (Trifolium repens), red clover (Trifolium pratense) or perennial ryegrass (Lolium perenne)

Abstract: Two experiments were performed with post-valve T-cannulated growing pigs, using five animals in each experiment in a change-over design to evaluate the effect of inclusion of four different dried forage meals on ileal crude protein (CP) and amino acid (AA) digestibilities. The control diets (C1 and C2) were barley-based and the experimental diets were formulated by replacing the barley with 100 or 200 g/kg of either lucerne (Medicago sativa) or white clover (Trifolium repens) meal in Expt 1 and red clover (Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…L. perenne (perennial ryegrass) is a grass species that is considered to be of very high quality nutritionally, due to its levels of energy, sugar and protein in relation to other grass species (Edwards et al, 2007;Williams et al, 2007). The gross energy content of the L. perenne in the present study was similar to that described by Lindberg and Andersson (1998) and Reverter et al (1999) (these two studies from the literature appear to have used the same pasture), although the pasture in the present study had a greater crude protein content. The amino acid profile in the present study was similar to that reported for L. perenne by Reverter et al (1999), but the concentration of each amino acid was greater in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…L. perenne (perennial ryegrass) is a grass species that is considered to be of very high quality nutritionally, due to its levels of energy, sugar and protein in relation to other grass species (Edwards et al, 2007;Williams et al, 2007). The gross energy content of the L. perenne in the present study was similar to that described by Lindberg and Andersson (1998) and Reverter et al (1999) (these two studies from the literature appear to have used the same pasture), although the pasture in the present study had a greater crude protein content. The amino acid profile in the present study was similar to that reported for L. perenne by Reverter et al (1999), but the concentration of each amino acid was greater in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…In pigs, inclusion of pea fibre in a wheat diet tended to increase the output of mucins in the ileal digesta from 6.1 to 7.3 g per day for diets supplemented with 0 and 240 g of pea fibre per day, respectively (Lien, Sauer, & He, 2001). Similarly ileal glucosamine and galactosamine excretion increased continuously with fibre intake (Reverter, Lundh, & Lindberg, 1999). When wheat bran (150 g/kg diet dry matter) was added to a protein-free diet for pigs, the ileal output of galactosamine at the terminal ileum increased from 1.93 to 4.13 g per day (Fuller & Cadenhead, 1991).…”
Section: Alteration In Gastric Emptying and Rate Of Passagementioning
confidence: 96%
“…soy hulls (Dilger et al, 2004), hulls of faba beans (Jansman et al, 1995), alfalfa leaf meal (Reverter et al, 1999). Accordingly the ID of AA were improved due to dehulling e.g.…”
Section: Introductionmentioning
confidence: 99%